COMPREHENSIVE SEXUALITY EDUCATION PROGRAM FOR ELEMENTARY SCHOOL CHILDREN - Fadhilah, Ningsih; Mulawarman, Mulawarman; Mulyani, Petra Kristi (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
Sexuality education for children school base is foundation important in to form attitudes, behaviors, and skills taking healthy decision related relationships and boundaries personal. Individual capable make right decision, develop draft positive self and relationships and prevent impact negative to health sexual. The purpose of study this is for to explore room scope material that needs to be strengthened in give understanding sexuality education and determining factors the success of the sexuality education program for child age Elementary School. Review literature systematic used in study this, is done use framework PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) work, explores practice based on evidence, effectiveness, and challenges in implementation of educational programs sexuality for child Age 6–12 years. Procedure this PRISMA research done through four steps namely identification, screening, eligibility and inclusion. At this stage identification done search text through three databases namely Science Direct, Taylor and Francis and Eric.ed.gov. and obtained results 8 matching articles with criteria. The result study this that room scope in carry out sexuality education for children need notice environment inclusive and participatory active. Effective sexuality education must create a stigma - free and inviting environment participation active from students, need designed with to discuss Topic sensitive in a way open and safe, at the same time overcoming the shame and stigma that often accompanies stick to the topic sexual. Education based on family need done with collaborative between schools and parents, emphasizing importance communication between parents and children related protection self and personal boundaries. The factors that influence the success of sexuality education is teacher perception, age, gender, and culture as well as the necessary delivery strategies customized with development child age school base.